A new species of the Genus Delphinium (Ranunculaceae) from Lahul Valley of Himachal Pradesh, India - Agnihotri, Priyanka; Husain, Danish; Husain, Tariq (Phytotaxa, 2014)
A new species of Delphinium (Ranunculaceace) is described and illustrated from Lahul valley of Himachal Pradesh, India. Its affinities with the allied species D. viscosum and D. cashmerianum are discussed. It differs from closely allied species in having bracteoles with hooked apex, shape of spur that resembles parrot’s beak, staminode with dense hoard of hairs at ventral apex, hairs in single line on the inner surface of ovary and cleft stigma.